Obesity and Asthma Risk in Indonesian Adults: Findings from the 2018 Indonesia Basic Health Research - Nisa, Hoirun (Kesmas, 2023)
Obesity and asthma are both global public health challenges. Mounting evidence suggests that obesity may increase asthma risk in adults; however, the association by sex remains uncertain. This study examined the association of obesity with asthma risk in Indonesian adult men and women. Data were obtained from the 2018 Indonesia Basic Health Research. The analysis included 299,837 men and 333,218 women aged ≥18 years. Asthma was identified by the self-report of a doctor’s diagnosis. Obesity was defined as a body mass index ≥30 kg/m2. A logistic regression was used for data analysis. Asthma prevalence was 2.7% (2.5% in men and 2.8% in women) and was higher in obese than non-obese adults. The adjusted odds ratio (aOR) of having asthma-related obesity was 1.22, 95% Confidence Interval (CI) = 1.17–1.28 (aOR = 1.25, 95% CI = 1.21–1.34 in women and aOR = 1.14, 95% CI = 1.05–1.25 in men). In conclusion, asthma prevalence was relatively low in Indonesian adults and slightly higher in women than men. Both men and women had a slight increase in the odds of having asthma-related obesity. Longitudinal studies are needed to understand better the causality association of obesity with asthma in adults.